Orthorhombic modification of bis[4-(3-pyridylmethylideneamino) phenyl]methane - Shah, K.; Shah, M.R.; Khan, I.U.; Ng, S.W. (International Union of Crystallography, 2010)
The title compound, C(25)H(20)N(4), is a disubstituted methane derivative having two pyridylmethyleneaminophenyl arms, one of which is essentially rigid as all atoms lie on a plane (r.m.s. deviation = 0.074 angstrom), whereas the other is twisted [ dihedral angle between the phenylene and pyridyl rings = 51.1 (4)degrees]. The angle at the methylene C atom is 113.2 (2)degrees.